La pobreza, ¿una cuestión femenina? : pobreza y género en España en los datos de la ECV 2009 = Poverty : a feminine issue? Gender and poverty in SpainSLIC data 2009 - Belzunegui, Angel; Pastor, Inma; Valls, Francesc (Comunitania. Revista Internacional de Trabajo Social y Ciencias Sociales, 2011)
In this article some analyses and reflexions are presented, beginning with the data of exploitation from the Income and Living Conditions Survey, within the “Poverty and Gender in Spain” investigation project (financed by the Woman’s Institute). An analysis of poverty in terms of gender has been made, originating from the evolution of the global poverty ratio, as well as that of the factors that may explain the poverty differential between men and women. Considering this data, we believe it relevant to ask ourselves about the concept of feminization of poverty and its empirical basis, in order to conclude that, taking into account the higher percentage of poverty in women than in men, the differential may not be sufficient enough for us to assert that there is a feminization of poverty understood as a process in which the differences between male and female poverty are expanding. En este artículo se presentan algunos análisis y reflexiones a partir de los datos de la explotación de la Encuesta de Condiciones de Vida, dentro del proyecto de investigación “Pobreza y género en España” (financiado por el Instituto de la Mujer). Se ha realizado un análisis de la pobreza en función del género, a partir de la evolución de las tasas de pobreza globales y de los factores que pueden explicar el diferencial de pobreza entre hombres y mujeres. A la vista de estos datos, nos parece pertinente preguntarnos sobre el concepto de feminización de la pobreza y sobre su base empírica, para concluir que, si bien se constatan mayores tasas de pobreza en mujeres que en hombres, puede que el diferencial no sea suficiente como para poder afirmar que existe una feminización de la pobreza entendida esta como un proceso en el que se van ensanchando las diferencias entre la pobreza femenina y la masculina